2016
DOI: 10.1369/0022155416646089
|View full text |Cite
|
Sign up to set email alerts
|

Post-Irradiated Human Submandibular Glands Display High Collagen Deposition, Disorganized Cell Junctions, and an Increased Number of Adipocytes

Abstract: Salivary glands are vital for maintaining oral health. Head and neck radiation therapy is one of the most common causes of salivary gland hypofunction. Little is known about the structural changes that occur in salivary glands after radiation therapy. The aim of this study is to understand the structural changes that occur in post-irradiated human (submandibular gland [SMG]) as compared with untreated ones. We determined changes in epithelial polarity, presence of collagen deposition, and alteration in adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Severe radiation injury to the salivary glands results in depletion of acinar cells, concomitant with ductal expansion, and an increase in fibrosis and inflammation (Cheng et al 2011; Nam et al 2016). Secretory cell loss appears to be a late effect, as SMG acinar cell depletion is not obvious at 2 or 6 wk following irradiation (Appendix Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Severe radiation injury to the salivary glands results in depletion of acinar cells, concomitant with ductal expansion, and an increase in fibrosis and inflammation (Cheng et al 2011; Nam et al 2016). Secretory cell loss appears to be a late effect, as SMG acinar cell depletion is not obvious at 2 or 6 wk following irradiation (Appendix Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In salivary glands of SS patients and NOD mice, the integrity of TJs is disrupted, including elevated Cldn1 and Cldn3 expression as well as reduced Cldn4, Ocln, and ZO‐1 expression (Zhang et al , 2016). ZO‐1 is also observed to be decreased in post‐irradiated human SMG (Nam et al , 2016). Moreover, the expression of ZO‐1, Cldn3, and Cldn11 are reduced in the hyposecretory SMG, whereas these TJ proteins levels are reversed with the restoration of SMG function (Cong et al , 2012; Yang et al , 2017).…”
Section: Discussionmentioning
confidence: 97%
“…In our study, the depletion of salivary ductal progenitors and acinar cells was observed 4 wk after IR and persisted 12 wk after IR. IR injury to the salivary glands depletes salivary gland progenitors and increases fibrosis and inflammation (Cheng et al 2011; Nam et al 2016). However, immunofluorescence analysis showed the preservation of KRT14 + basal ductal and MIST1 + acinar cells in SMGs subjected to retroductal EGF treatment before IR.…”
Section: Discussionmentioning
confidence: 99%